2013
DOI: 10.1155/2013/784743
|View full text |Cite
|
Sign up to set email alerts
|

New Method of Depositing the Nanostructured Amorphous Carbon for Carbon Based Solar Cell Applications

Abstract: Nanostructured amorphous carbon (a-C) solar cells were successfully deposited via a self-designed aerosol-assisted chemical vapor deposition (AACVD). The fabricated solar cell with the configuration of Au/p-C/n-Si/Au achieved efficiency ( ) of 1.72 × 10 −4 % for device deposited at 500 ∘ C, 1.24 × 10 −4 % for 450 ∘ C, and 0.03 × 10 −4 % for 400 ∘ C. Photoresponse characteristic was highlighted under illumination (AM 1.5 illuminations: 100 mW/cm 2 , 25 ∘ C), where conductivity increased when the sample was bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Carbon black synthesis requires temperatures as high as 2000°C, 21 and a-C is typically deposited by plasma-enhanced chemical vapor deposition (CVD) 22,23 although aerosol-assisted CVD has recently been demonstrated. 8 While extensive research has been conducted to develop solution-based methods of graphene deposition, rGO films remain several orders of magnitude less conductive than CVD graphene. 16,24,25 In contrast to the widely studied world of synthetic carbonaceous materials, the optical and electronic properties (and corresponding range of tunability) of natural carbonaceous materials are still poorly understood.…”
Section: * S Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon black synthesis requires temperatures as high as 2000°C, 21 and a-C is typically deposited by plasma-enhanced chemical vapor deposition (CVD) 22,23 although aerosol-assisted CVD has recently been demonstrated. 8 While extensive research has been conducted to develop solution-based methods of graphene deposition, rGO films remain several orders of magnitude less conductive than CVD graphene. 16,24,25 In contrast to the widely studied world of synthetic carbonaceous materials, the optical and electronic properties (and corresponding range of tunability) of natural carbonaceous materials are still poorly understood.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Graphitic materials and amorphous carbon (a-C) , are the leading and a promising candidate, respectively, for anode materials in lithium ion batteries. Amorphous carbon has also been used in the manufacturing of transistors , and photovoltaic devices, , and nanostructured graphitic materials (such as graphene and reduced graphene oxide) have gained significant attention for applications including in photovoltaics, transparent conductive membranes, and Joule heating devices. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it also could be observed that a sharp absorption edge at wavelength of about 410 nm indicates the absorption properties of P3HT at visible range [9]. These I-V measurements prove that the P3HT behaviour is able to serve as conductive channels for the transport of electrons for optical properties [10]. The measurement was done in under illumination condition AM 1.5 illumination (100 mW/cm ,25 C).…”
Section: Glass Substratementioning
confidence: 54%